1998
DOI: 10.1002/(sici)1097-0274(199810)34:4<373::aid-ajim11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Relative chronic effects of different occupational dusts on respiratory indices and health of workers in three Ethiopian factories

Abstract: The respiratory effects of dusts in different sections of yarn, cement, and cigarette factories were studied in 211 nonsmoking male and female workers aged 21–57 years. The controls used were 211 healthy nonsmoking and nonexposed male and female subjects aged 20–57 years from the general population. Forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1), FEV1/FVC ratio, forced expiratory flow (FEF200–1,200 ml), forced mid‐expiratory flow (FMF25–75%) and peak expiratory flow rate (PEFR) were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 12 publications
2
30
0
1
Order By: Relevance
“…The age and employment distributions among the workers in our surveys were of similar magnitude to findings in other cement studies (33,36,38,41,54). Since the study included the major cement producing factories in Malaysia (33,41).…”
Section: External Validitysupporting
confidence: 89%
See 1 more Smart Citation
“…The age and employment distributions among the workers in our surveys were of similar magnitude to findings in other cement studies (33,36,38,41,54). Since the study included the major cement producing factories in Malaysia (33,41).…”
Section: External Validitysupporting
confidence: 89%
“…A list of studies on cement dust exposure published in scientific journals the last 15 years (except for one American study published 23 years ago) is shown in Table 1. Higher dust exposure has been reported in developing countries such as Tanzania, Ethiopia, Iran and Saudi Arabia (33,(36)(37)(38) than in USA and Norway (39,40). This difference might be caused by established regulatory actions and more advanced technical control measures in the cement industry in industrialized countries than in developing countries.…”
Section: Occupational Dust Exposure In the Cement Industrymentioning
confidence: 93%
“…selected populations such as factory workers and miners). [40][41][42] COPD is not often recognised as respiratory symptoms are frequently attributed to smoking, to respiratory infections such as tuberculosis, or to ageing. Furthermore, the term COPD is unfamiliar to the public and even to physicians in many parts of sub-Saharan Africa.…”
Section: Prevalence Of Copdmentioning
confidence: 99%
“…Diseases of the respiratory system induced by occupational dusts are influenced by the type of dust and duration of exposure [2]. Occupational diseases are caused by pathologic responses of the workers to their working environment [3].…”
Section: Introductionmentioning
confidence: 99%